1998
DOI: 10.1093/oxfordjournals.molbev.a025898
|View full text |Cite
|
Sign up to set email alerts
|

Substitution bias, rapid saturation, and the use of mtDNA for nematode systematics

Abstract: Only relatively recently have researchers turned to molecular methods for nematode phylogeny reconstruction. Thus, we lack the extensive literature on evolutionary patterns and phylogenetic usefulness of different DNA regions for nematodes that exists for other taxa. Here, we examine the usefulness of mtDNA for nematode phylogeny reconstruction and provide data that can be used for a priori character weighting or for parameter specification in models of sequence evolution. We estimated the substitution pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
126
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(147 citation statements)
references
References 40 publications
19
126
1
1
Order By: Relevance
“…Blouin et al 1998, Peng et al 2007, Jex et al 2009), allowing high resolution in deep analyses of closely related lineages (Callejón et al 2012). However, when comparing rDNA and cox1 data alone, support of branches is higher in trees based on nuclear data.…”
Section: Discussionmentioning
confidence: 99%
“…Blouin et al 1998, Peng et al 2007, Jex et al 2009), allowing high resolution in deep analyses of closely related lineages (Callejón et al 2012). However, when comparing rDNA and cox1 data alone, support of branches is higher in trees based on nuclear data.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, analyses of the substitution patterns for mtDNA genes of nematodes have suggested that they are very useful markers for identifying and differentiating cryptic species and for determining relationships of closely related species (Blouin et al,1998;Blouin, 2002;Hu et al, 2004 andreferences therein, Hu &Gasser, 2006). The same mtDNA region was demonstrated to be useful in distinguishing closely related anisakid taxa previously characterized by allozyme markers, belonging to the genus Anisakis (Valentini et al, 2006), and to the genus Contracaecum maturing in fish-eating birds .…”
Section: Discussionmentioning
confidence: 99%
“…cox1 mtDNA was also sequenced from nematodes found in cavity and vent. The cox1 mtDNA is considered to evolve faster than rDNA (Blouin et al 1998), but again, no clear differences in the cox1 sequence were observed between the vent larvae and those from the body cavity, and between individuals with polymorphisms in their ITS rDNA. There is insufficient data to comment on whether the 2 conserved nucleotide/amino acid differences in the cox1 sequence between anisakid specimens infecting RVS salmon and those infecting herring populations around the British Isles (Cross et al 2007) is due to species or population differences.…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 99%